2020
DOI: 10.1016/j.ejon.2020.101844
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of cancer nurses working in four European countries: A qualitative study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Only one study (reported on in two papers) did not meet the 60% threshold for quality assessment due to a lack of a clear research question (50, 64). Findings from this study were not consequential to the change model due to these being reinforced by other studies (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study (reported on in two papers) did not meet the 60% threshold for quality assessment due to a lack of a clear research question (50, 64). Findings from this study were not consequential to the change model due to these being reinforced by other studies (50).…”
Section: Resultsmentioning
confidence: 99%
“…Research was located in 32 countries across six continents (Table 2). Two studies were located in multiple 367 countries (50,51). One study did not state the study location (52).…”
Section: Data Abstraction and Synthesismentioning
confidence: 99%
“… 10 Policy reforms in some countries have expanded nurses’ clinical practice to incorporate specialisations and activities such as independent prescribing. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…While literature exists investigating the practice of oncology nurses 17 and those working within advanced practice roles, 11 there is a paucity when exploring haematology nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the CSN is a registered nurse with specialist knowledge in specific cancer care and treatment who can offer continuous expert and accessible care, who is a key worker and advocates for the diagnosed persons, and who provides support to the persons diagnosed with CRC and their family members (Buckley et al, 2018;Luck et al, 2017;Cook et al, 2021). Due to the evolving cancer care over the past few decades, the CSN's role has expanded (Buckley et al, 2018;Charalambous et al, 2018;Lemonde and Payman, 2015;Cook et al, 2021;Kelly et al, 2020). Nowadays, apart from supportive care, it includes working collaboratively with and educating other professions and ensuring effective communication (Buckley et al, 2018;Luck et al, 2017;Cook et al, 2021).…”
Section: Introductionmentioning
confidence: 99%